Social Determinants of Health: reflections from the origins of the "social issues" - Souza, Diego de Oliveira; Silva, Sóstenes Ericson Vicente da; Silva, Neuzianne de Oliveira (Saúde e Sociedade, 2013)
In this article we analyze what has been called the Social Determinants of Health (SDH). This is a literature review in which we turn to the some authors who deal on the subject in an attempt to reconsider the theme under the marxist theory. In contrast to the theory of SDH, we recovered the foundations of the "social issues", seeking to demonstrate the essential determination of health issues. We have seen that the theoretical approach of the SDH deal with social problems as if they were fragments of reality that gain autonomy. Nevertheless, in reality they are a single question - the "social issues" - with its material origin (and also human and social) intertwined to the work process such as it is established under capitalism. Therefore, it is in the process of capital accumulation that we find the essential determination of health issues and hence its solution requires the dissolution of the bourgeois social order.